RNA splicing based on reporter genes system: Detection, imaging and applications - Shi, Xiaorui; Won, Miae; Tang, Chu; Ding, Qihang; Sharma, Amit; Wang, Fu; Kim, Jong Seung (Coordination chemistry reviews, 2023)
[Display omitted] •RNA splicing is an essential process that governs many aspects of gene expression.•The three main types of RNA splicing are pre-mRNA splicing, group Ⅰ and Ⅱ introns self-splicing.•Reporter system for visualization of RNA splicing mainly includes fluorescent and bioluminescent proteins, SMaRT, ribozyme and radionuclide reporter.•Reporter system can be employed to screen splicing regulators, inhibitors, variants and detect splicing efficiency and sites. The RNA splicing process which removes introns from nascent transcripts is an indispensable step in gene expression. The life processes of organisms are composed of a range of different mRNA variants that are translated into proteins with various functions as a result of alternative splicing. Monitoring and controlling RNA splicing can successfully repair the dangerous mutant genes that underlie various diseases. However, attempts to uncover specific elements in the regulation of splicing are hampered by the absence of appropriate tools. Traditional RNA splicing detection technology frequently focuses on the identification and analysis of post-splicing products, which is often accompanied by irreversible damage to the detected objects. It cannot provide dynamic and detailed descriptions of regulatory factors, functional elements, and spatiotemporal distributions during the splicing process. It is still difficult to identify and measure aberrant RNA splicing in living cells and in vivo. New technical tools have sprung up, providing fresh motivation and guidance for the identification of RNA splicing. Here, based on the genetically encoded reporter gene system, we cover in detail the monitoring, imaging and biomedical applications of RNA splicing process using different types of reporter gene systems.